2006
DOI: 10.1159/000094748
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid/Carboxymethylcellulose Membrane Barrier versus Taurolidine for the Prevention of Adhesions to Polypropylene Mesh

Abstract: Background: A hyaluronic acid/carboxymethylcellulose (HA/CMC) membrane is an effective measure to prevent polypropylene mesh induced adhesions. We hypothesized that taurolidine 2% solution might be a cost-effective alternative to decrease adhesion formation. Materials and Methods: Twenty-four rats were randomized into three groups: mesh alone (group 1), mesh + taurolidine 2% (group 2), and mesh + HA/CMC (group 3). Polypropylene mesh (4 cm2) was used to repair surgically induced anterior abdominal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…As compared to results recently published in the literature using Adept® (Baxter Healthcare Corporation, USA) [28,29,30,31,32,33], Interceed® (Ethicon, Inc., USA) [25,27,29,34,35,36,37,38,39], and Seprafilm® (Genzyme Corporation, USA) [26,27,31,34,38,39,40,41,42,43,44] in rat models, the results obtained with 4DryField PH in this study are in the upper range of benefit and are comparable with the data of Kaptanoglu et al [43] and Wallwiener et al [29]. …”
Section: Discussionmentioning
confidence: 96%
“…As compared to results recently published in the literature using Adept® (Baxter Healthcare Corporation, USA) [28,29,30,31,32,33], Interceed® (Ethicon, Inc., USA) [25,27,29,34,35,36,37,38,39], and Seprafilm® (Genzyme Corporation, USA) [26,27,31,34,38,39,40,41,42,43,44] in rat models, the results obtained with 4DryField PH in this study are in the upper range of benefit and are comparable with the data of Kaptanoglu et al [43] and Wallwiener et al [29]. …”
Section: Discussionmentioning
confidence: 96%
“…Many experimental and clinical studies have revealed that taurolidine has significant antiadherent activity on pathogen microorganisms, and although the data are conflicting, possibly decreases postoperative peritoneal adhesion formations. [17][18][19]27 Opitz et al 17 showed in an experimental study that the use of heparin and taurolidine led to a significant reduction of intraperitoneal tumor growth, however, did not decrease the severity of adhesions. In contrast, a recent study comparing the effectiveness of Seprafilm \ and taurolidine revealed similar results when the products were used for the purpose of preventing mesh-induced adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…16 Finally, experimental studies have demonstrated that the product may be used as an antiadhesive, probably as a consequence of its antimicrobial and antiproliferative effects. [17][18][19] In addition, advantages, such as cost effectiveness and liquid form of the product, may lead the acceptance of its use in open and laparoscopic surgery.…”
mentioning
confidence: 99%
“…Other authors have, however, seen an increase in adhesions after antibiotic abdominal irrigation [46] . The bactericidal taurolidine has reduced adhesions experimentally [47] . Chemotherapeutics such as 5-FU [48] and mitomycin C [49] have also been evaluated and demonstrated to reduce the extent of adhesions.…”
Section: Other Medical Interventionsmentioning
confidence: 98%